2006
DOI: 10.1207/s15430154jce2103_12
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cancer Diagnosis on the Lifestyle and Habits of Patients Served at a Veterans Administration Hospital

Abstract: Although many veterans may adopt healthier habits after cancer diagnosis, a larger portion of them do not, which highlights the need for further evaluation and implementation of educational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Systematically identifying and addressing patients' individual HRF profiles may have a great potential for at least two reasons: Firstly, it may simultaneously serve primary and secondary prevention purposes by preventing the onset of chronic diseases in patients who have not been diagnosed with chronic diseases yet, and by improving treatment success and prognosis in patients with chronic diseases. Although a large part of the general hospital patients is expected to have been diagnosed with chronic diseases in the past, our study supports previous findings showing that routine health care alone may not be sufficient for patients with chronic diseases to change their lifestyle [68,69]. Secondly, systematic multiple HRF screening and intervention may provide the means to reach most patients, including those most in need, namely male, older, lower educated, and unemployed patients as indicated by our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Systematically identifying and addressing patients' individual HRF profiles may have a great potential for at least two reasons: Firstly, it may simultaneously serve primary and secondary prevention purposes by preventing the onset of chronic diseases in patients who have not been diagnosed with chronic diseases yet, and by improving treatment success and prognosis in patients with chronic diseases. Although a large part of the general hospital patients is expected to have been diagnosed with chronic diseases in the past, our study supports previous findings showing that routine health care alone may not be sufficient for patients with chronic diseases to change their lifestyle [68,69]. Secondly, systematic multiple HRF screening and intervention may provide the means to reach most patients, including those most in need, namely male, older, lower educated, and unemployed patients as indicated by our findings.…”
Section: Discussionsupporting
confidence: 88%
“…However, the modification of certain habits is clearly difficult. According to Jazieh et al (8), less than a quarter of all patients with antecedents of cancer (mean age 68 years) modified their habit in a positive way. Smoking tobacco generates addiction as a result of its nicotine content, which acts upon the central nervous system, causing both physical and psychological dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, survivors who are older, male, or less educated may be less likely to engage in health promoting behavior changes [40,41]. Additionally, a study of survivors receiving care at a VA clinic indicated that after cancer diagnosis, only 35% of survivors increased their fruit and vegetable consumption; furthermore, 43% of survivors actually decreased their physical activity [42]. With incomplete adherence to healthy diet and exercise recommendations, achieving and maintaining a healthy body size may be challenging for many survivors.…”
Section: Discussionmentioning
confidence: 99%